Molecular Biology of Pancreatic Cancer: How Useful Is It in Clinical Practice? - Sakorafas, George H; Smyrniotis, Vasileios (JOP. Journal of the Pancreas, 2012)
Context During the recent two decades dramatic advances of molecular biology allowed an in-depth understanding of pancreatic carcinogenesis. It is currently accepted that pancreatic cancer has a genetic component. The real challenge is now how these impressive advances could be used in clinical practice. Objective To critically present currently available data regarding clinical application of molecular biology in pancreatic cancer. Methods Reports about clinical implications of molecular biology in patients with pancreatic cancer were retrieved from PubMed. These reports were selected on the basis of their clinical relevance, and the data of their publication (preferentially within the last 5 years). Emphasis was placed on reports investigating diagnostic, prognostic, and therapeutic implications. Results Molecular biology can be used to identify individuals at high-risk for pancreatic cancer development. Intensive surveillance is indicated in these patients to detect pancreatic neoplasia ideally at a preinvasive stage, when curative resection is still possible. Molecular biology can also be used in the diagnosis of pancreatic cancer, with molecular analysis on samples of biologic material, such as serum or plasma, duodenal fluid or preferentially pure pancreatic juice, pancreatic cells or tissue, and stools. Molecular indices have also prognostic significance. Finally, molecular biology may have therapeutic implications by using various therapeutic approaches, such as antiangiogenic factors, purine synthesis inhibitors, matrix metalloproteinase inhibitors, factors modulating tumor-stroma interaction, inactivation of the hedgehog pathway, gene therapy, oncolytic viral therapy, immunotherapy (both passive as well as active) etc. Conclusion Molecular biology may have important clinical implications in patients with pancreatic cancer and represents one of the most active areas on cancer research. Hopefully clinical applications of molecular biology in pancreatic cancer will expand in the future, improving the effectiveness of treatment and prognosis of patients with pancreatic cancer.